Cuentos viejos o diálogo con el universo - Rubio Torres, Carlos Alberto (2007)
Cuentos Viejos (Old Tales) a book written by María Leal de Noguera, published in different editions between 1923 and 1945, may be considered a milestone in the foundations of a Costa Rican literature for the younger generations. It is a collection of fairy tales full of knowledge and wisdom, that have been treasured in different places of the world. This article intends to prove the above, through an analysis of “La Mano Peluda” (“The Hairy Hand”) which unveils the fact that the text is a dialogue with very old myths: The Greek story about Eros and Psyche; and a story taken from the Indian “Panchatantra”, which describes the love between the nymph Urvasi and the mortal Pururavas.